2014
DOI: 10.4184/asj.2014.8.3.346
|View full text |Cite
|
Sign up to set email alerts
|

How Does Chronic Back Pain Influence Quality of Life in Koreans: A Cross-Sectional Study

Abstract: Study DesignA cross-sectional study.PurposeTo explore the impact of chronic low back pain (CLBP) on individuals' quality of life; to understand current treatment practices and level of satisfaction with treatment in patients with CLBP.Overview of LiteratureAssessing subjective, patient-reported outcomes such as quality of life is essential to health care research.MethodsInfluences of the CLBP were analyzed via a questionnaire, which contained the character of CLBP, effect of pain management, Korean version Osw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…Hence, Silva et al reported that global pain intensity was the most important predictor of disability in patients with musculoskeletal pain in a cross-sectional study [61]; similar results were also reported by other authors [62,63]. Disability has been reported to be correlated with pain severity/intensity according to cross-sectional studies of LBP and neck pain [64][65][66]. Miedema at al.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Hence, Silva et al reported that global pain intensity was the most important predictor of disability in patients with musculoskeletal pain in a cross-sectional study [61]; similar results were also reported by other authors [62,63]. Disability has been reported to be correlated with pain severity/intensity according to cross-sectional studies of LBP and neck pain [64][65][66]. Miedema at al.…”
Section: Discussionsupporting
confidence: 66%
“…Cross-sectional analyses have reported a negative correlation between neck pain or LBP and aspects of HRQoL [66,[71][72][73][74]. Such relationships have been found both in chronic pain cohorts and in population-based studies [75][76][77].…”
Section: Discussionmentioning
confidence: 88%
“…Cross-sectional analyses have reported a negative correlation between back pain and aspects of HRQoL. 7,13,22,39,41,51 Such relationships have been found both in chronic pain cohorts and in population-based studies. 4,32,43 In addition, systematic reviews have confirmed evidence for a link between pain and low HRQoL.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, QoL measurements in people with chronic disease are useful for assessing general disease impact [6,7]. Several previous studies have reported the negative impact of knee pain and LBP on QoL [8‐12]. However, few studies have compared the effects of both diseases on QoL in the same investigation.…”
Section: Introductionmentioning
confidence: 99%